Implementation and Certification of ISO/IEC 29110 in an IT Startup in Peru - García Paucar, Luis Hernán (2015)
This article presents the implementation of ISO/IEC 29110 in a four-person IT startup company in Peru. After completing the implementation of the ISO/IEC 29110 project management and software implementation processes using an agile approach, the next step was to execute these processes in a project with an actual customer: software that facilitates communication between clients and legal consultants at the second-largest insurance companies in Peru. Managing the project and developing the software took about 900 hours. Using ISO/ IEC 29110 software engineering practices enabled the startup to plan and execute the project while expending only 18 percent of the total project effort on rework (i.e., wasted effort). In this article, the authors also describe the steps and the effort required by the VSE to be granted an ISO/IEC 29110 certificate of conformity. The startup became the first Peruvian VSE to obtain an ISO/IEC 29110 certification. The ISO/IEC 29110 certification facilitated access to new clients and larger projects.